Respon Tanaman Kangkung (Ipomea reptans Poir) Terhadap Beberapa Jenis Dan Dosis Pupuk Kandang - Dewi Rambu Baba Lalu; Yonce Melyanus Killa; Suryani K.K.L Kapoe (Prodi Agroteknologi dan Agribisnis - Universitas Kristen Wira Wacana Sumba, 2023)
Kale plants are plants that are popular with the community and are rich in nutritional sources. One way to increase the production of kale plants is to provide fertilizers such as horse and chicken manure. The purpose of this study that is determine the response of water spinach (I. reptans Poir) to several types and doses of manure. This research was conducted in May-August 2022 in Hambala Village, Waingapu City District, East Sumba Regency. Experiments in this study using completely randomized design (CRD) with 4 treatments, namely PK1 (chicken manure 2.5 tons/ha = 22.68 g/polybag); PK2 (chicken manure 5 tons/ha = 45.37 g/polybag); PK3 (horse manure 2.5 tonnes/ha = 22.68 g/polybag); PK4 (horse manure 5 tons / ha = 45.37 g/polybag). The results of the study found that the best fertilizer application that affected plant height and number of leaves was chicken manure at a dose of 2.5 tons/ha, while for fresh weight the best result was horse manure at a dose of 2.5 tons/ha.